Therochemical Conversion of Biomass: An Overview - Pragya Yadav; A.K Sharma (International Journal of Energy and Thermal Applications, 2024)
A viable way to utilize biomass resources for energy production is through thermochemical conversion processes. This study presents a thorough analysis of the principles, workings, benefits, and drawbacks of thermochemical conversion processes, such as pyrolysis, gasification, and combustion. We examine the various uses of thermochemical conversion in waste management, biofuel synthesis, and energy production. We also go over recent developments, technological breakthroughs, and potential future paths for biomass thermochemistry research. This review attempts to contribute to a deeper understanding of thermochemical conversion processes and their role in advancing sustainable energy solutions by synthesizing current knowledge and research findings.
Keywords: Biofuels; biomass; combustion; gasification; pyrolysis; thermochemical conversion